Aluminum-doped zinc oxide electrode capable of transmitting ultraviolet light and preparation method thereof
AZO films are prepared by high-energy atomic beam and pulsed laser sputtering deposition methods, which solves the problem of low transmittance to the ultraviolet band, and achieves the combination of high transmittance and low resistance, meeting the needs of high-performance solar cells and other equipment.
Patent Information
- Application Number
- CN202411096778.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The existing AZO film has a low transmittance to the ultraviolet band, making it difficult to meet the needs of cutting-edge blue-light-ultraviolet light-emitting diodes, blue-light-ultraviolet photodetectors, high-performance solar cells and other equipment.
Aluminum-doped zinc oxide (AZO) film was prepared by high-energy atomic beam. The laser energy density, frequency and substrate heating temperature were adjusted by pulsed laser sputtering deposition method to prepare a high transmittance AZO electrode.
It achieves high transmittance of AZO film in the UV UVA band, with an average transmittance of up to 85%, while maintaining low resistance characteristics, meeting the needs of high-performance solar cells and other equipment.
Smart Images

Figure CN118996356B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transparent conductive film materials, and in particular relates to an aluminum-doped zinc oxide electrode that can transmit ultraviolet light and a preparation method thereof. Background Art
[0002] In recent years, transparent conductive oxides (TCO) have been shining in the field of new optoelectronic devices due to their high transmittance and low resistance, such as light-emitting diodes (LEDs), photodetectors, flat-panel liquid crystal displays, solar cells, etc. At present, the mainstream material of TCO film is indium tin oxide (ITO), but indium is a rare element with a scarce and expensive content, and is not environmentally friendly. Compared with ITO, aluminum-doped zinc oxide (AZO) has the characteristics of rich raw material content, low price, green and non-toxic, and excellent optoelectronic properties. It is currently recognized as the best substitute for ITO film. According to previous studies, the resistivity of AZO film can reach 1×10 -4 Ωcm, and its transmittance in the visible light region can reach more than 85%, making it an excellent transparent conductive material.
[0003] However, the transmittance of AZO film in the ultraviolet region is low. If the transmittance of AZO film in the ultraviolet band can be improved, it can meet the requirements of cutting-edge blue-ultraviolet light-emitting diodes, blue-ultraviolet photodetectors, high-performance solar cells, etc. for ultraviolet-transmissive electrode films. AlGaN is widely used in ultraviolet LEDs because of its large bandgap, excellent photoelectric performance, and good response to the ultraviolet band. Ultraviolet LEDs based on AlGaN materials have the advantages of small size, low power consumption, high light efficiency, and low price, but they still have challenges in terms of photoelectric conversion efficiency, light source stability, and lifespan. Therefore, ultraviolet-transmissive AZO films will have great potential to replace AlGaN in ultraviolet LEDs.
[0004] At present, there are many methods for preparing AZO thin films, mainly including molecular beam epitaxy (MBE), magnetron sputtering, chemical vapor deposition (CVD), pulsed laser deposition (PLD), spray pyrolysis, electron beam evaporation, sol-gel method, etc. Among them, the pulsed laser sputtering deposition method has the advantages of high atomic beam energy, low working vacuum, and low substrate temperature requirement compared with other thin film preparation methods. It can make the doped atoms more effectively achieve substitutional doping and activation, and provide a basis for the realization of ultraviolet AZO electrodes. For example, Chinese invention patent CN102453869A uses magnetron sputtering to obtain an AZO film with a resistance of 0.9E-3Ω to 6.5E-3Ω and an ultraviolet UVA transmittance of 20%-40%; patent CN102312201A uses physical vapor deposition to obtain an AZO film with a resistance of 3E-4Ω to 8E-4Ω, a transmittance of 0 in the ultraviolet band of 300nm-380nm, and an average transmittance of 20% in the 380nm-400nm band. However, the transmittance of AZO thin films prepared by traditional coating methods such as magnetron sputtering and physical vapor deposition is low in the ultraviolet band. For example, the transmittance of thin films prepared by magnetron sputtering is low in the ultraviolet band, especially the transmittance at 300nm-370nm is 0, and it gradually becomes transparent after 370nm, and the transmittance at 370nm-400nm is about 37%. Therefore, it is necessary to develop a method for AZO thin films with high transmittance in the ultraviolet UVA band. Summary of the invention
[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing an AZO film with high transmittance in the ultraviolet UVA band by using a high-energy atomic beam, so as to overcome the problem of poor transmittance of the AZO film in the UVA band and maintain the low resistance characteristics of the AZO film, so that it can meet the requirements of cutting-edge blue-ultraviolet light-emitting diodes, blue-ultraviolet photodetectors, high-performance solar cells, etc. for ultraviolet-transmissive electrode films.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A first aspect of the present invention provides a method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light, the method comprising the following steps:
[0008] S1, using aluminum oxide and zinc oxide as targets, and placing the targets in a sputtering chamber;
[0009] S2. Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target, and then evacuate the chamber to a pressure below 5E-5Pa;
[0010] S3, heat the substrate to above 300°C, and adjust the pulse width of the pulse laser to 10-30ns, the wavelength to 200-300nm, and the energy density to 5-17J / cm 2 , energy is 100-300mJ, frequency is 3-20Hz; then the laser is focused to no more than 2mm 2 The target material in the sputtering chamber is irradiated with a light spot and sputtered for 10-40 minutes to obtain an aluminum-doped zinc oxide (AZO) electrode that is transparent to ultraviolet light on the substrate.
[0011] The method of the present invention sputters a suitable target material by high-energy pulse laser in a vacuum environment, and heats the substrate so that the adsorbed atoms obtain sufficient diffusion kinetic energy, and finally obtains an AZO electrode that can transmit ultraviolet light. The resistivity of the obtained AZO electrode ranges from 7.8E-4Ω·cm to 1.3E-3Ω·cm, and the average transmittance in the visible light band (400-760nm) is about 70% to 90%, and the transmittance in the near ultraviolet UVA band (320-400nm) is about 60%-85%.
[0012] Preferably, the heating temperature of the substrate is 400-500°C.
[0013] Preferably, the pulse laser energy is 150-200 mJ.
[0014] Preferably, the pulse laser frequency is 3-10 Hz.
[0015] The present invention adopts a pulsed laser sputtering deposition method, uses a high energy density pulsed laser to strip the target material, and then prepares the AZO film. By adopting a suitable process, such as a working gas pressure lower than 5E-5Pa, a pulse energy of 150-200mJ, a pulsed laser frequency of 3-10Hz, and a laser focus spot area of less than 2mm 2 (ensuring sufficient laser energy density), the substrate is heated to above 300°C (optimally 400-500°C); and then an AZO electrode that can transmit ultraviolet light is obtained. The method of the present invention can be used to obtain an AZO film of uniform thickness on a glass substrate. The obtained AZO film transparent electrode is flat and dense, with a resistivity as low as 2.8E-3Ω·cm, an average transmittance of up to 90% in the visible light band (400-760nm), and a transmittance of up to 85% in the near-ultraviolet UVA band (320-400nm), which can meet the requirements of cutting-edge blue-ultraviolet light-emitting diodes, blue-ultraviolet photodetectors, high-performance solar cells, etc. for ultraviolet-transmissive electrode films.
[0016] Compared with traditional coating methods such as magnetron sputtering and physical vapor deposition, the present invention increases the optical band gap of AZO film to more than 3.8eV, and the optimal transmittance in ultraviolet UVA (320-400nm) can reach more than 80%. Compared with other pulsed laser deposition methods, the present invention adopts the best growth kinetic conditions according to the characteristics of AZO film, and the transmittance of the obtained AZO film in the ultraviolet UVA band is increased by about 3 times under the premise of equivalent resistivity.
[0017] Preferably, the distance between the substrate and the target is 30 to 90 mm.
[0018] Preferably, the weight ratio of aluminum oxide to zinc oxide is 2:98-5:95.
[0019] Preferably, the substrate includes (but is not limited to) high temperature resistant glass and polymer plastic.
[0020] Preferably, the substrate is first ultrasonically cleaned in alcohol or acetone and then rinsed with water before use.
[0021] The second aspect of the present invention provides an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light and is prepared by the preparation method described in the first aspect.
[0022] The third aspect of the present invention provides the use of the ultraviolet-transmissive aluminum-doped zinc oxide electrode described in the second aspect in a photoelectric device, wherein the photoelectric device includes a blue-ultraviolet light-emitting diode, a blue-ultraviolet photodetector, and a solar cell.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention discloses a method for preparing an aluminum-doped zinc oxide (AZO) electrode that is transparent to ultraviolet light. The method adopts a pulsed laser sputtering deposition method, with aluminum oxide and zinc oxide as target materials, and the AZO film is prepared by adopting appropriate pulsed laser energy density, pulsed laser frequency, substrate heating temperature and other processes. The method of the present invention can obtain an AZO film with uniform thickness on a glass substrate. The obtained AZO film transparent electrode is flat and dense, with a resistivity as low as 2.8E-3Ω·cm, an average transmittance of up to 90% in the visible light band (400-760nm), and a transmittance of up to 85% in the near-ultraviolet UVA band (320-400nm), which can meet the requirements of cutting-edge blue-ultraviolet light-emitting diodes, blue-ultraviolet photodetectors, high-performance solar cells, etc. for ultraviolet transparent electrode films. Specifically, the present invention has the following advantages:
[0025] (1) Compared with coating methods such as magnetron sputtering, the present invention adopts a pulsed laser deposition sputtering method, which can adjust the laser to process the target material into a single-atom plasma, which is beneficial to the substitutional doping and activation of doping atoms, thereby increasing the carrier concentration and its optical band gap, so that the prepared AZO film has a low resistivity and is transparent to the UVA ultraviolet band, thereby giving the AZO film the potential for application in ultraviolet-related electronic devices;
[0026] (2) Compared with the existing pulse laser coating method, the present invention focuses the laser to a higher energy according to the growth principle of aluminum-doped zinc oxide, and heats the coating substrate at a higher temperature to obtain the optimal atomic crystallization kinetic conditions, so as to improve the crystallinity of aluminum-doped zinc oxide and reduce its defect rate, thereby reducing the influence of amorphous components and material defects on ultraviolet light absorption and scattering, so that its transmittance in the near-ultraviolet UVA band meets the needs of industrial applications, making the application of AZO thin films in ultraviolet-related electronic devices feasible;
[0027] (3) The method of the present invention is used to prepare AZO thin films with good repeatability and high controllability. Thin films with different resistivities and UV transmittances can be prepared by adjusting parameters as needed. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation of AZO thin films using pulsed laser sputtering method.
[0029] Figure 2 Schematic diagram of the excellent transmittance of aluminum-doped zinc oxide electrode to ultraviolet light.
[0030] Figure 3 XRD patterns of AZO thin films prepared by pulsed laser sputtering at different glass substrate temperatures.
[0031] Figure 4 Transmission spectra of AZO films prepared at different glass substrate temperatures using pulsed laser sputtering.
[0032] Figure 5 Optical band gap diagram of AZO thin films prepared by pulsed laser sputtering method at different glass substrate temperatures.
[0033] Figure 6 This is the average transmission spectrum of AZO films prepared by pulsed laser sputtering at different glass substrate temperatures in the UVA band.
[0034] Figure 7 Resistivity diagram of AZO thin films prepared at different glass substrate temperatures using pulsed laser sputtering method.
[0035] Figure 8Transmission spectra of AZO films prepared by pulsed laser sputtering at different laser energies and frequencies. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0037] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0038] Example 1: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0039] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0040] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0041] (2) Select ultraviolet-transmissive high-temperature glass (quartz glass) as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0042] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating to make the substrate temperature reach 500 °C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 20Hz; then the laser is focused to 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0043] (4) Take out the substrate and test and analyze the film. Figure 2 As shown in the figure, the AZO film has an obvious c-axis orientation and a (002) peak is found. Its full-band transmittance is as follows: Figure 3 As shown, the average transmittance of 300nm-900nm is 87.4%, of which the average transmittance of UVA band (320-400nm) is 77.1% ( Figure 5), the average transmittance in the visible light band (400-760nm) is 91.5%, and the average transmittance in the infrared light band (760-900) is 91.6%. Figure 4 As shown in Figure 2, the optical band gap width is calculated to be 3.86 eV by using the film transmittance. Figure 6 As shown, the resistivity of the film is 5.8E-4Ω·cm.
[0044] Example 2: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0045] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0046] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0047] (2) Select ultraviolet-transmissive high-temperature glass (quartz glass) as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0048] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn off the substrate heating and keep the substrate temperature at room temperature. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 20Hz; then the laser is focused to 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0049] The average transmittance of the film at 300nm-900nm is 67.4% ( Figure 3 ), of which the average transmittance of UVA band (320-400nm) is 42.4% ( Figure 5 ), the average transmittance in the visible light band (400-760nm) is 71.5%, and the average transmittance in the infrared light band (760-900) is 79.3%. The resistivity is 1.3E-3Ω·cm( Figure 6 ).
[0050] Example 3: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0051] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0052] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0053] (2) Select ultraviolet-transmissive high-temperature glass (quartz glass) as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0054] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating and heat the substrate temperature to 400 °C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 20Hz; then the laser focus is 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0055] The average transmittance of the film at 300nm-900nm is 85.7% ( Figure 3 ), of which the average transmittance of UVA band (320-400nm) is 75.9% ( Figure 5 ), the average transmittance in the visible light band (400-760nm) is 89.3%, and the average transmittance in the infrared light band (760-900) is 90.1%. The resistivity is 5.3E-4Ω·cm( Figure 6 ).
[0056] Example 4: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0057] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0058] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0059] (2) Select high temperature resistant glass (quartz glass) that can transmit ultraviolet light as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0060] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating and heat the substrate temperature to 300 °C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 20Hz; then the laser is focused to 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0061] The average transmittance of the film at 300nm-900nm is 81.1% ( Figure 3 ), of which the average transmittance of UVA band (320-400nm) is 66.8% ( Figure 5 ), the average transmittance in the visible light band (400-760nm) is 85.1%, and the average transmittance in the infrared light band (760-900) is 86.7%. The resistivity is 6.4E-4Ω·cm( Figure 6 ).
[0062] Example 5: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0063] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0064] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0065] (2) Select high temperature resistant glass (quartz glass) that can transmit ultraviolet light as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0066] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating and heat the substrate temperature to 200 °C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 20Hz; then the laser focus is 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0067] The average transmittance of the film at 300nm-900nm is 74.1% ( Figure 3 ), of which the average transmittance of UVA band (320-400nm) is 55.4% ( Figure 5 ), the average transmittance in the visible light band (400-760nm) is 78.1%, and the average transmittance in the infrared light band (760-900) is 82.5%. The resistivity is 7.8E-4Ω·cm( Figure 6 ).
[0068] Example 6: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0069] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0070] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0071] (2) Select high temperature resistant glass (quartz glass) that can transmit ultraviolet light as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0072] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating to make the substrate temperature reach 400°C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 7.5 J / cm 2 , energy is 150mJ, frequency is 5Hz; then the laser is focused to 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot and sputtered for 40 minutes to obtain an AZO thin film on the substrate.
[0073] The average transmittance of the film at 300nm-900nm is 93% ( Figure 3 ), the average transmittance of the film to UVA ultraviolet band (320-400nm) is 84.1% ( Figure 5 ), the resistivity is 4.76E-3Ω·cm( Figure 6 ).
[0074] Example 7: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0075] like Figure 1 As shown, the preparation method of the aluminum-doped zinc oxide electrode comprises the following steps:
[0076] (1) Select an AZO circular target with a weight ratio of aluminum oxide to zinc oxide of 2:98 and place the circular target in a sputtering chamber.
[0077] (2) Select high temperature resistant glass (quartz glass) that can transmit ultraviolet light as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0078] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, and evacuate the chamber to a pressure below 5E-5 Pa. Then turn on the substrate heating to make the substrate temperature reach 400 °C. Then turn on the pulse laser and adjust the pulse width of the pulse laser to 20 ns, the wavelength to 248 nm, and the energy density to 16.5 J / cm 2 , energy is 330mJ, frequency is 20Hz; then the laser is focused to 2mm 2 The AZO circular target in the sputtering chamber was irradiated with a light spot, and the sputtering lasted for 10 minutes to obtain an AZO thin film on the substrate.
[0079] The average transmittance of the film at 300nm-900nm is 80.6% ( Figure 3 ), the average transmittance of the film to UVA ultraviolet band (320-400nm) is 63.8% ( Figure 5 ), the resistivity is 2.8E-3Ω·cm( Figure 6 ). It can be seen that the use of high energy density actually reduces the transmittance. In addition, Figure 7 As shown, the UVA transmittance of AZO prepared after 40 minutes of laser sputtering with 150 mJ and 5 Hz frequency is the best, which is 84.1%. After increasing the laser energy and frequency, the transmittance of the film decreases significantly.
[0080] Comparative Example 1: A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light
[0081] (1) Using AZO circular target with a mass ratio of aluminum oxide to zinc oxide of 2:98, DC magnetron sputtering was used to deposit AZO thin films.
[0082] (2) Select high temperature resistant glass (quartz glass) that can transmit ultraviolet light as the substrate, then ultrasonically clean the substrate in alcohol and acetone for 10-30 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes;
[0083] (3) Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target to 60 mm, turn on the mechanical pump and molecular pump to evacuate to 5E-3 Pa, then fill the working gas with high-purity argon (99.99%) until the vacuum chamber pressure is 0.15 Pa, and heat the substrate to 400°C. Turn on the DC power supply (current power is 100W) for pre-sputtering for 10 minutes. The sputtering time is 30 minutes, and an AZO film is obtained on the substrate.
[0084] The film transmittance at 300nm-370nm is 0, the average transmittance at 300-900nm band is 60%-65%, and the average transmittance to UVA ultraviolet band (320-400nm) is 30%-35%.
[0085] In summary, the present invention optimizes the preparation method and process conditions of aluminum-doped zinc oxide electrodes specifically for ultraviolet transmittance. The aluminum-doped zinc oxide electrode prepared by the method of the present invention has a transmittance of up to 84.3% in the UVA ultraviolet band, reaching the standard of more than 80% required for industrial applications. Compared with other pulsed laser sputtering methods, the present invention optimizes the preparation method and process conditions of aluminum-doped zinc oxide electrodes specifically for ultraviolet transmittance. The transmittance of aluminum-doped zinc oxide electrodes prepared by the method of the present invention in the UVA ultraviolet band can reach up to 84.3%, reaching the standard of more than 80% required for industrial applications. Compared with other pulsed laser sputtering methods, the present invention optimizes the preparation method and process conditions of aluminum-doped zinc oxide electrodes by selecting a substrate temperature above 400°C and selecting an optimal pulsed laser energy density (e.g. 7.5 J / cm 2 ), and select the optimal pulse laser frequency (such as 5Hz), thereby improving the ultraviolet band transmittance of the AZO material. Compared with AZO films prepared by other pulse laser sputtering deposition methods, the absorption edge of the AZO film prepared by the method of the present invention is significantly blue-shifted, especially at 340nm-350nm, which can reach more than 80%, and is completely transparent to ultraviolet light, so that it meets the requirements of cutting-edge blue-ultraviolet light-emitting diodes, blue-ultraviolet photodetectors, high-performance solar cells, etc. for ultraviolet-transparent electrode films ( Figure 8 ), while the transmittance of AZO films prepared by other pulsed laser sputtering deposition methods is low in this band and cannot meet the requirements of industrial applications.
[0086] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
Claims
1. A method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light, characterized in that: The following steps are involved: S1, using aluminum oxide and zinc oxide as targets, and placing the targets in a sputtering chamber; S2. Place the substrate in the sputtering chamber, adjust the distance between the substrate and the target, and then evacuate the chamber to a pressure below 5E-5Pa; S3, heat the substrate to above 300°C, and adjust the pulse width of the pulse laser to 10-30ns, the wavelength to 200-300nm, and the energy density to 5-17J / cm 2 , energy is 100-300mJ, frequency is 3-20Hz; then the laser is focused to no more than 2mm 2 The target material in the sputtering chamber is irradiated with a light spot and sputtered for 10-40 minutes to obtain an aluminum-doped zinc oxide (AZO) electrode that is transparent to ultraviolet light on the substrate.
2. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The heating temperature of the substrate is 400-500°C.
3. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The pulse laser energy is 150-200mJ.
4. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The pulse laser frequency is 3-10 Hz.
5. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The distance between the substrate and the target is 30 to 90 mm.
6. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The weight ratio of aluminum oxide to zinc oxide is 2:98-5:
95.
7. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The substrate includes high temperature resistant glass and polymer plastic.
8. The method for preparing an aluminum-doped zinc oxide electrode that is transparent to ultraviolet light according to claim 1, characterized in that: The substrate is firstly ultrasonically cleaned in alcohol and acetone before use, and then rinsed with water.
9. An aluminum-doped zinc oxide electrode that is transparent to ultraviolet light and is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ultraviolet-transmissive aluminum-doped zinc oxide electrode according to claim 9 in a photoelectric device, characterized in that: The optoelectronic device includes a blue-ultraviolet light emitting diode, a blue-ultraviolet photodetector, and a solar cell.
Citation Information
Patent Citations
Preparation method of Al-doped zinc oxide transparent conductive thin film
CN102312201A
Preparation method and application of aluminum-doped zinc oxide conductive film
CN102453869A